Design of Sports Event Evaluation and Classification Method Based on Deep Neural Network. (18th April 2022) - Zhao, Shutong; Sun, Jiangang
Abstract : Large-scale sports events with high-level competition as the main content will have a great impact on the host city whether from the economic level or from the social level. With the improvement of human civilization, people realize that the holding of large-scale sports events not only has a positive impact on the economy and society but also brings some negative effects, such as waste of resources and environmental pollution, which have attracted the attention of the government and investors. Therefore, how to scientifically, comprehensively, and reasonably evaluate large-scale sports events, especially the accurate evaluation of their economic and social effects, has become the focus of attention. The evaluation of large-scale sports events mainly includes two levels: economic and social. Through the specific analysis of the evaluation content and the weight calculation of the evaluation index, the overall optimization of the evaluation of large-scale sports events is realized, and the reference experience is provided for the holding and evaluation of large-scale sports events in the future. Based on this, this article proposes a sports event evaluation and classification method based on the deep neural network. Firstly, on the basis of literature review and field investigation, the evaluation index system of sports events is established. Deep learning models have strong fitting power and robustness and have been applied to many real-world tasks. Then the deep neural network is used to evaluate the holding effect of sports events. The experimental results show that the model has high evaluation accuracy and is of great significance to the supervision and guidance of sports events.